2019
DOI: 10.3390/cancers11020229
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of 3-Bromopyruvate, an Anticancer Compound, Against Antibiotic-Susceptible and Antibiotic-Resistant Helicobacter pylori Strains

Abstract: Helicobacter pylori (H. pylori) is a bacterium capable of inducing chronic active gastritis, which in some people, develops into gastric cancers. One of the substances that may be useful in the eradication of this microorganism is 3-Bromopyruvate (3-BP), an anticancer compound with antimicrobial properties. The aim of this article was to determine the activity of 3-BP against antibiotic-susceptible and antibiotic-resistant H. pylori strains. The antimicrobial activity was determined using a disk-diffusion meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 61 publications
(91 reference statements)
1
44
0
Order By: Relevance
“…In a collection of eight articles [37][38][39][40][41][42][43][44] showing a morphological effect of antibiotics and other substances classically used in H. pylori therapies, microscopic and culture methods were used. In four of them [38,39,42,43], different staining techniques and fluorescence analysis were additionally included ( Table 1 and Figure 1).…”
Section: Antibiotics and Proton Pump Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a collection of eight articles [37][38][39][40][41][42][43][44] showing a morphological effect of antibiotics and other substances classically used in H. pylori therapies, microscopic and culture methods were used. In four of them [38,39,42,43], different staining techniques and fluorescence analysis were additionally included ( Table 1 and Figure 1).…”
Section: Antibiotics and Proton Pump Inhibitorsmentioning
confidence: 99%
“…In the next five analyzed articles [38][39][40][41]43], observations regarding a morphostructural effect of antibiotics come from publications primarily focusing on new compounds with a potential anti-H. pylori activity. Narayana et al [38,39] showed that AMX within 24 h reduced the viability of H. pylori by 3 log when treated with MIC.…”
Section: Antibiotics and Proton Pump Inhibitorsmentioning
confidence: 99%
“…After 48 h of incubation at 37 • C under microaerobic conditions, microbial growth was colorimetric, revealed by the addition of 0.1 mg/mL resazurin (Sigma-Aldrich). The interaction between drugs was determined according to the fractional inhibitory concentration index (FICI): FIC A (MIC A in the presence of B/MIC A alone) + FIC B (MIC B in the presence of A/MIC B alone) [24].…”
Section: Checkerboard Assaysmentioning
confidence: 99%
“…We analysed the in vitro bactericidal effect of lithocholic acid in combination with other recognized anti-H. pylori substances including the conventional antibiotics clarithromycin, metronidazole and levofloxacin, as well as the flavonoid chrysin [16], by the checkerboard method [16,17,24,28]. According to this approach, when two antimicrobial substances are used together in a fixed concentration ratio against a certain microbial strain, and the combinatory action of both drugs noticeably increases the activity of each drug when they act separately against the same strain, we could infer that these substances exhibit a synergistic interaction in their antimicrobial action.…”
Section: Lithocholic Acid Partially Synergizes With Other Antimicrobimentioning
confidence: 99%
See 1 more Smart Citation